2021
DOI: 10.18502/jri.v22i4.7652
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Cases of Pure Malignant Germ Cell Tumors of the Ovary: A Case Series on 10 Years Experience at a Tertiary Care Center

Abstract: Background: Malignant ovarian germ cell tumors (MOGCTs) are rare female cancers, constituting  up to 10% of ovarian cancers. Dysgerminoma is the most common histological variant. Surgical removal of the tumor with optimal debulking is the treatment of choice. Multidrug chemotherapy following surgery offers high remission rates. Considering the prevalence of these tumors in adolescent and young females, fertility-sparing treatment is of paramount importance. Methods: The data of all patients with ovarian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Germ cell tumors mainly affect prepubertal and pubertal youth; immature teratomas are frequently associated with ectodermal sinus tumors and dysgerminomas 4 . Within genetic studies, the presence of the Y chromosome has been found in the karyotype of some pediatric patients with gonadal dysgenesis, which is a risk factor for developing a dysgerminoma 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Germ cell tumors mainly affect prepubertal and pubertal youth; immature teratomas are frequently associated with ectodermal sinus tumors and dysgerminomas 4 . Within genetic studies, the presence of the Y chromosome has been found in the karyotype of some pediatric patients with gonadal dysgenesis, which is a risk factor for developing a dysgerminoma 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Mixed GCT represents 8% of cases of GCT. 4 They rarely have more than two subtypes. Our patient had four subtypes including yolk sac tumor, embryonal carcinoma, immature teratoma, and dysgerminoma.…”
Section: Rare Case Of Rosai-dorfman Disease Linked To a Mixed Maligna...mentioning
confidence: 99%
“…Delays in diagnosis may result in the tumors reaching an advanced stage, limiting treatment options and overall survival. Therefore, understanding the latest trends and advancements in diagnosing and treating these tumors is crucial to improving patient outcomes [ 2 ].…”
Section: Introductionmentioning
confidence: 99%